Analysis of Sanitary Hygiene Quality and Germ Rate in the Home Industry Chips - Faizah, Faizah; Ningsih, Riyan; Syamsir, Syamsir (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Food Poisoning Extraordinary Events (KLB KP) are often not fully reported, with the vast majority of cases not being recorded. In 2019, there were 77 KP KLB cases in Indonesia, especially in West Sumatra, with most cases caused by unhygienic household processed foods. Judging from the type of food that causes food poisoning, household processed food has the largest percentage compared to snack food, food service food, and processed food The number of KP KLB reports does not always indicate the level of food safety. Objective : The purpose of the study was to determine the relationship between the quality of sanitary hygiene and the presence of germs in cooking utensils in the home industry of chips in Tanjung Selor Floating Village. Research Methods/ Implementation Methods : The research design used is a type of correlation descriptive research with a cross sectional design where this research is measured or observed at the same time at one time. The population in this study is the entire home chip industry of Tanjung Selor Floating Village as many as 7 home industries, with the Total sampling technique. The research instrument used observation sheets and interviews, analyzed using the Chi-Square Test. Results : The results of the statistical test were obtained from the relationship between personal hygiene and sanitation of cookware storage and the presence of germ numbers (pValue=0.048). Meanwhile, the relationship between cooking ware washing techniques and cooking utensils sanitation with the presence of germ numbers (pValue=0.143). Conclusion/Lesson Learned : The conclusion and suggestion of this study is that there is a relationship between personal hygiene and sanitation of cookware storage and the existence of germ numbers in the chip home industry in Tanjung Selor Floating Village. There is no relationship between cooking ware washing techniques and cooking utensils sanitation and the existence of germs in the chip industry home of Tanjung Selor Floating Village. It is recommended to the local government to increase supervision and guidance on the home industry.